Pengembangan Media Pembelajaran Video Interaktif Berbasis Powtoon Pada Materi Sistem Ekskresi untuk Meningkatkan Hasil Belajar Siswa SMP - Salma Azkiya; Ratna Yulinda; Yudha Irhasyuarna (CV.ITTC INDONESIA, 2025)
The process of creating learning materials in the form of interactive Powtoon videos with the aim of achieving a high level of validity, usability, and efficacy in helping junior high school students to improve their learning outcomes regarding the excretory system is the main focus of this research. Analysis, design, development, implementation, and evaluation are the five main stages of the ADDIE development model, which is the methodology used in this study for research and development (R&D). Tests to measure learning outcomes, student response questionnaires, and expert validation sheets are some of the methods used to collect data. Data analysis was conducted through validity testing using Aiken's V formula, practicality evaluation based on the percentage of student responses, and effectiveness analysis using the N-Gain value approach. The validation results obtained a score of 0.88, which shows that the media is in a very valid category. Meanwhile, the practicality level of the media reached 86%, indicating that the media is very practical to use. In terms of effectiveness, the N-Gain value of 0.67 is classified as moderate. Based on these overall findings, it can be concluded that Powtoon-based interactive videos are feasible as an alternative science learning media that is innovative, effective, and relevant in supporting students' understanding of excretory system material at the junior high school level.